Spatial Variation and Possible Sources Assessment at Federal Territory of Kuala Lumpur Water Treatment Plan Using Chemometric Technique - M. Zolkipli, H.; Juahir, H.; Adiana, G.; Zainuddin, N.; B.H.M. Maliki, A.; Z. Mohamed, S.; N.W. A. Halim, W.; F. Sa’adon, N.; S. Mohamed, N.; A.A. Hashim, N. (International Journal of Engineering and Technology, 2018)
This study aims to identify the possible sources in drinking water parameters heavy metal and organic parameters (HMOPs) and spatial variation between untreated water and treated water at Federal Territory of Kuala Lumpur water treatment plant. The indicator HMOPs in drinking water in Kuala Lumpur were selected as parameters to discriminate the possible source of water treatment plants (WTPs) pollutant. Chemometric technique such as principal component analysis (PCA) and discriminant analysis (DA) was identified based on the five years’ availability data starting from 2012 to 2016. PCA were used to identify the most significant parameters which are highlighted eleven strong factors loading of parameter respectively out of sixteen for PCs and classified as possible sources in WTPs. Continue with DA analysis that is successful distinguish two categories region in WTP using the forward stepwise and backward stepwise with significant amount is 98.46%. From this study, we can conclude that this chemometric is the best technique of analysis to get a lot of information such as identify possible sources of pollutant and discriminant of two station sampling categories that will give novelty to Malaysian Ministry of Health (MOH) and collaboration agency in National Drinking Water Quality Surveillances Program (NDWQSP).